A new synonym of Rohdea annulata (Asparagaceae) and the first report of its wild distribution in China - Hu, Guang-Wan (Phytotaxa, 2019)
Tupistra annulata H.Li & J.L.Huang in Huang & Li (1990: 51) was described based on the materials from cultivated plants in Kunming Botanical Garden, and its precise wild collecting locality was unknown. Its perianth with a ringed, fleshy, smooth, cushion like appendage in throat makes it distinctly different from other species in the genus. Tamura et al. (2000) separated Campylandra Baker (1875: 582) from Tupistra Ker Gawler (1814: 1655) and transferred this species into Campylandra as C. annulata (H.Li & J.L.Huang) Tamura et al. (2000: 159). Later, Tanaka (2003) transferred some species of Campylandra, Tupistra and Gonioscypha Baker (1875: 581) into Rohdea Roth (1821: 196) based on morphological analysis but not including Campylandra annulata. Supported by the evidence from parsimony analysis of trnK and rbcL sequences and karyotype data, Yamashita & Tamura (2004) merged the whole genus Campylandra in Rohdea. Therefore this species was combined as R. annulata (H.Li & J.L.Huang) Yamashita & Tamura (2004: 369).